The main issues of protection of the environment and people’s health in the Republic of Kazakhstan - Rakhmetulina Б.С.; Myrzakhanov Е.Н. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article discusses current problems of environmental safety in the state. The authors highlight the organizational and legal aspects of environmental protection. Practical experience is studied, whose activities are aimed at suppressing threats to environmental safety. "Green development" is the current international standard, which makes it possible to divide the development of the world community into the ideology of "economic" in the last 60 years and "green" in the next 60 years. Green development is based on the theory of green systems, i.e. the interdependence and mutual influence of humanity and nature. Green manufacturing theory means saving and investing in resources, increasing efficiency, cleaner production, reusing and recycling materials. Green growth means stimulating economic growth and development while ensuring that natural assets are preserved and continue to provide the resources and ecosystem services on which our well-being depends. The purpose of the study is to identify effective measures to protect the environment. When studying this problem, data and empirical materials in the field of environmental protection were used.The only evidence of this is voluntary closure of the world’s largest nuclear test site, international promotion of the Aral Sea and Caspian protection programs, as well as other experienced works of Kazakhstan to protect the environment from harmful effects occurring at the international level. The annual messages of our President, as usual, are aimed at distinguishing our achievements, orienting our future, and most importantly, jointly defining the right way to achieve the great goal common to all of us.